Assessing In-Depth Vocabulary Ability of Adult ESL Learners - Nadarajan, Shanthi (Language Society and Culture, University of Tasmania, Australia, 2008)
This study examines the in depth vocabulary ability of L2 learners in a foreign language and immersion setting. Using an in-depth vocabulary knowledge test, the researcher examined L2 learners’ ability to recognize the various word meanings of 40 words and their collocations. Using L1 speakers word performance data for the same test, the study indicates that it is possible for advanced L2 learners in immersion settings to attain near native fluency in terms of word collocation skills for specific word ranges. The study also revealed that most L2 learners do not know the different meanings of words and this often affected the way they used a word. The study has implications for teaching and learning of academic vocabulary in the language classroom.